Isolasi dan Karakterisasi Jamur Pendegradasi Katekin dari Seresah Pinus - Elisa Nurnawati; Langkah Sembiring (Biota : Jurnal Ilmiah Ilmu-Ilmu Hayati, 2003)
Isolation of catechin-degrading fungus from pine litter samples was done using minimal medium that containing catechin as sole carbon and energy source.  A total of 53 isolates were chosen to represent different colonial types of catechin degrading-fungus. The isolates were screened for their ability to degrade catechin in three stages. The first stage of screening was based on their ability to grow on solid medium containing 2 mM, and as a result, 28 isolates were selected.  The second stage of screening on the same medium but containing 4 mM of catechin resulting in 14 selected isolates. The third stage screening was based on their mean growth rate constant (k), instantaneous growth rate constant (m) and generation time (g) on minimal medium containing 4 mM catechin. The result showed that four isolates (D9, K2, K11, and S11) were the best catechin degradator. Further growth kinetic study  (k, m ,and g) of selected  isolates   indicated that  D9, K2, and S11 grew well on the medium containing 40 mM, but  K11 was inhibited by concentration of higher than 10 mM. Catechin biodegradation process was determined by following the decrease of catechin concentration on liquid medium. It was found that isolate K2 had higher ability to degrade catechin than the isolate K11. Finally, the four selected isolates from the third stage were characterized in terms of macroscopic, microscopic and phenotypic characters and identified. The result of the study showed that the isolates D9, K2 and S11 were identified as member of Aspergillus niger group. The isolate D9 was very similar to isolate S11, while the isolate K2 was found to be the most similar with Aspergillus niger van Tiegh. IFO 6341. The isolate K11 was assigned to be member of the genus Trichoderma.